Bury your gays ebook - Tingle, Chuck (2024)
The instant USA Today bestseller by Chuck Tingle about what it takes to succeed in a world that wants you dead. Named o ne of the Best Horror Books of 2024 ( Esquire, Parade, and Library Journal) ! Misha knows that chasing success in Hollywood can be hell. But finally, after years of trying to make it, his big moment is here: an Oscar nomination. And the executives at the studio for his long-running streaming series know just the thing to kick his career to the next level: kill off the gay characters, "for the algorithm," in the upcoming season finale. Misha refuses, but he soon realizes that he's just put a target on his back. And what's worse, monsters from his horror movie days are stalking him and his friends through the hills above Los Angeles. Haunted by his past, Misha must risk his entire future—before the horrors from the silver screen find a way to bury him for good. "Brilliantly bloody, wildly fun, and extremely scary, Bury Your Gays brings a sledgehammer down on tired tropes and makes a masterpiece of their guts." —Rachel Harrison, national bestselling author of Black Sheep Also by Chuck Tingle Lucky Day Camp Damascus Straight At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.